A newly synthesized platinum-based compound (PBC-II) increases chemosensitivity of HeLa ovarian cancer cells via inhibition of autophagy - Moureq Rashed Alotaibi; Homood Moqbel As Sobeai; Faten Abdullah Alaqil; Mashal Almutairi; Khalid Alhazzani; Adam A.A. Sulaiman; Anvarhusein A. Isab; Nasser Hadal Alotaibi (Elsevier, 2019)
There are many mechanisms of resistance, chemoresistance of HeLa cells to anti-cancer agents seems to be autophagy-mediated. While using very effective anti-cancers such as Doxorubicin and cisplatin, cells overcome the cytotoxicity of these drugs through promotion of what so-called cytoprotective autophagy. Here in this study, we sought to introduce a novel platinum-based compound PBC-II that possesses anti-cancer activity. Our data showed that PBC-II is able to induce apoptosis at relatively low concentrations, with no detectable reactive oxygen species (ROS). However, further experiments demonstrated that exposure of HeLa cells to PBC-II did not promote autophagy; rather, it resulted in accumulation of p62 and decrease in LC3-II levels. Autophagy was then promoted in HeLa cells pharmacologically by Doxorubicin and genetically by siRNA IL-10. In order to confirm promotion of autophagy in our model, we performed acridine orange staining to assess for autophagy under microscope as well as via flow cytometry. We then measured protein level of autophagy markers p62 and LC3 by western blot. Our data indicated that PBC-II interferes with therapy-induced autophagy. We also determined PI3K activity while co-incubation of PBC-II with autophagy inducers. It was clear that PI3K activation decreased when PBC-II was co-administered with autophagy inducers. Collectively, PBC-II exerts unique anti-proliferative effects associated with inhibition of autophagy, which indicates that PBC-II is potentially a promising agent to be used in resistant ovarian tumors. Keywords: Ovarian, Autophagy, Doxorubicin, IL-10, Platinum, HeLa